Prevalence, Etiology and Treatment of Peri‐Implant Mucositis and Peri‐Implantitis: A Survey of Periodontists in the United States. Issue 5 (1st May 2016) - Papathanasiou, Evangelos; Finkelman, Matthew; Hanley, James; Parashis, Andreas O.
Abstract : Background: Currently, information available on the exact prevalence and standard therapeutic protocol of peri‐implant diseases is insufficient. The aim of this survey was to investigate the perceived prevalence, etiology, and management of peri‐implant mucositis and peri‐implantitis by periodontists in the United States. Methods: A twenty‐question survey was developed. Periodontists currently practicing in the United States were contacted by an e‐mail that contained a link to access the survey. Results: Two hundred eighty periodontists (79.3% males; 62.9% with >10 years in practice, 75.7% in private practice) completed the survey. Most (96.1%) of the participants were placing implants (58.3% for >10 years and 32.4% >150 implants/year). The majority reported that the prevalence of peri‐implant mucositis and peri‐implantitis in their practices is up to 25% but is higher in the general US population and that up to 10% of implants must be removed due to peri‐implantitis. There was agreement among contributing etiologic factors such as: 1) plaque; 2) smoking; 3) adverse loading; 4) oral hygiene; 5) use of antimicrobial gel/mouthrinse; 6) non‐surgical debridement; 7) use of systemic antibiotics; and 8) 3‐month supportive care for treatment of peri‐implantitis. Significant heterogeneity was recorded in relation to the instruments used for debridement, use and type of surgical treatment, and materials used for regeneration. Only 5.1% believed that treatment is very effective. Conclusions: This survey indicates that peri‐implant diseases are a frequently encountered problem in periodontal practices and that the absence of a standard therapeutic protocol results in significant empirical use of therapeutic modalities and a moderately effective treatment outcome.